How valuable is ascitic cytology in the detection and management of malignancy?. Issue 931 (1st May 2003) - Karoo, R O S; Lloyd, T D R; Garcea, G; Redway, H D; Robertson, G S R
Abstract : Introduction: Ascitic cytology is often requested in the early stages of ascitic assessment. A review of this practice in a major English teaching hospital is presented. Method: Patients were retrospectively identified using the histopathology and patient administration system between January 1999 and May 2001. Results: Of 276 samples sent for assessment 35 cases were found to be negative when on further review an intra-abdominal malignancy was present. The malignancy was diagnosed using a radiological modality. The sensitivity of ascitic cytology was found to be 60% with 100% specificity. A delay of up to five days could be incurred awaiting the cytology results before further radiological examinations were undertaken. Conclusion: Too much hope is placed on ascitic cytology to provide the diagnosis at the expense of other investigations. It is recommended that the initial assessment should concentrate on history, examination, and basic tests on ascitic fluid to assess the serum-ascites albumin gradient. Ovarian malignancy is the only tumour type yielding a significant rate of detection from cytology with some prognostic impact. Results should not be awaited before abdominal ultrasound is undertaken. This more directed practice would help reduce unnecessary workload for the pathologist and has resource implications.